Diversification of risk of a fundamental portfolio based on semi-variance - Rutkowska-Ziarko, Anna; Garsztka, Przemysław (Economics and Business Review, 2014)
The following considerations are based on the concept of the fundamental portfolio as was proposed by [Tarczyński 1995]. In addition, in this article semi-variance, as an alternative to variance, was used as a measure of risk. The paper aims to propose and present empirical verification of the iterative algorithm for risk diversification in a fundamental portfolio with minimum semi-variance. The calculations were made assuming that we had a starting portfolio and that it could be modified to achieve the optimal solution under the established conditions The same calculations were performed for several starting portfolios.(original abstract)